EDUKASI PENCEGAHAN ANEMIA PADA IBU HAMIL DI KELURAHAN PASA GADANG KECAMATAN PADANG SELATAN KOTA PADANG - Melisa Yenti; Lianda Pangestica; Aissya Izzaty Hardian; M. Fadhilah (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Anemia was one of the leading causes of maternal mortality, with the 2018 Riset Kesehatan Dasar showing that 48.9% of pregnant women in Indonesia were affected. The high prevalence of anemia was primarily caused by nutritional deficiencies, which resulted from a lack of knowledge about proper nutritional needs during pregnancy. One preventive measure was the consumption of at least ninety Blood Additive Tablets (TTD) during pregnancy. An educational activity aimed to increase pregnant women’s knowledge about anemia prevention and the importance of consuming TTD. The methods used included lectures, discussions, distribution of educational materials like leaflets and posters, and sharing-hearing sessions. The success of the education program was measured based on the increase in participants' knowledge before and after the educational activity. The results showed an increase in the average knowledge score of pregnant women from 5.75 before the education to 9.25 after the education, with a p-value of 0.02. This indicated that the educational intervention was effective in improving knowledge. The use of health promotion materials, particularly leaflets, played a key role in enhancing understanding. It was expected that all pregnant women would consume TTD as recommended, and that health workers would regularly remind them of its importance. The activity was also intended to be conducted routinely to reduce the incidence of anemia among pregnant women.